Increasing Digital Literacy of PKK MSMEs through the Air Sempiang Bengkulu Village Library (Universitas Terbuka, 2024)
The Air Sempiang village library has an important role in increasing digital literacy for product development and marketing of Micro, Small, Medium Enterprise (MSMEs) which is managed by the village organization, namely the Family Welfare Empowerment (PKK) in MSMEs Air Sempiang village, Bengkulu. This research aims to determine the role of the Air Sempiang village library in increasing digital literacy of the Air Sempiang village PKK MSMEs, especially in the marketing sector. The research method used is a qualitative research method with a case study approach, data collection techniques used are interviews and literature studies, the data that has been obtained is analyzed using the data reduction stage, display data, and conclusion drawing. The results of the research show that members of the MSMEs PKK in Air Sempiang village utilize various collections in the Air Sempiang village library for product development. Apart from that, PKK MSMEs members also utilize collections related to digital marketing in the Air Sempiang village library as a reference source for marketing products on social media. The conclusion of this research is that the Air Sempiang village library plays an important role in accommodating the increase in digital literacy skills of the PKK MSMEs in Air Sempiang village, especially in utilizing collections to improve digital products and marketing